C# 10.0 all-in-one for dummies - Mueller, John Paul (For dummies, 2022)
Look sharp—learn or refresh your C# skills with the latest version C# is one of the most popular programming languages, and frequent updates help it keep pace as the world of coding changes. You can keep pace too, thanks to C# 10.0 All-in-One For Dummies, where you'll learn the basics of the language itself, how to code in Visual Studio, and how to take advantage of the new features in the latest release. At every stage of your career, you'll need to know the cutting-edge trends and techniques that clients want. This book has your back, with info on object-oriented programming, writing secure code, building web applications, and more. The six standalone mini-books you'll find inside this all-in-one will take you through the changes to C# and the practical applications and dev tools that you need to know. New features covered include records, init only setters, top-level statements, pattern matching enhancements, fit and finish features, and a lot more. Plus, this version is packed with more examples and code snippets, so you can sharply see C# in action! * Learn the very basics of C# programming, even if you have no prior experience * Refresh your knowledge of the language and learn how to use the new features in the 10.0 version release * Read six mini-books on hot coding topics like object-oriented programming, Visual Studio, and Windows 10 development * Enhance your employability and join the 6.5-million-strong community of C# developers You need an easy-to-read C# guide that will help you understand the incoming updates, and this For Dummies reference is it.